Peranan Musik Gereja Dalam Pembentukan Karakter Jemaat Dan Pembawa Misi Gereja di Gereja Bethany Indonesia Menara Doa Melonguane - Markus Wibowo (Program Studi Musik Gereja, Fakultas Seni dan Ilmu Sosial Keagamaan, IAKN Manado, 2020)
The study examines church music in Bethany Indonesia (GBI) Melonguane church service in Talaud Regency. The purpose of this study is to find out the role of church music for character education and church mission bearers precisely at Bethany Indonesia Church (GBI) Melauana Prayer Tower Church, Talaud Regency. From the results of the research exposure presented in the previous chapter, it can be concluded as a whole as follows: Church music has a good role in the context of the church's character education, this can occur because in the context of character education there are several understandings that the congregation should understand, namely; (1) Understanding music from the texts of the songs, (2) Understanding musicality, (3) Understanding theologically, and (4) Animation of music. Church music has a good role to play in the mission of the church. Every church must have its own mission. How to get the congregation involved in the mission of the church, namely by implementing any music sung (songs and songs) so that the music also lives in the soul of the congregation. Song texts that encourage the mission to be accompanied by musical understanding by singing it aesthetically good and theological understanding, the soul of a missionary from the congregation will appear, because the congregation first experience what is the prayer in the songs.